Cultivares de cártamo (Carthamus tinctorius L.) sob adubação nitrogenada em cobertura - Bueno, Paulo de Lima (2019)
Plants that are already grown thousands of years ago have shown surprisingly, relative efficiency in oil production. Among the several millenary plants, we can highlight the safflower (Carthamus tinctorius L.), which was originally used as a source of oil and pigments. Under this context, the objective of the present study was to evaluate the efficiency and the influence of the application on Nitrogen fertilizer (N) coverage in yield and grain oil content. The work was carried out in the city of Cascavel-PR, in two seasons, with two treatments, where the performance of safflower genotypes will be evaluated in relation to number of plants per meter, plant height, number of chapters per plant, oil content , protein. The data were tabulated in an Excel spreadsheet and afterwards an analysis of variance and comparison of averages by the Tuckey test with the aid of the software Assistat 7.5. Nitrogen fertilization had influence on plant height, number of chapters per plant, oil content and productivity and had no influence on oil content.